2013
DOI: 10.1093/cercor/bhs397
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity-Based Functional Analysis of Dopamine Release in the Striatum Using Diffusion-Weighted MRI and Positron Emission Tomography

Abstract: The striatum acts in conjunction with the cortex to control and execute functions that are impaired by abnormal dopamine neurotransmission in disorders such as Parkinson's and schizophrenia. To date, in vivo quantification of striatal dopamine has been restricted to structure-based striatal subdivisions. Here, we present a multimodal imaging approach that quantifies the endogenous dopamine release following the administration of d-amphetamine in the functional subdivisions of the striatum of healthy humans wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
341
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(367 citation statements)
references
References 62 publications
13
341
3
Order By: Relevance
“…[12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus). This is clearly superior to previous results by Stokes et al 11 and comparable to test-retest parameters obtained with high-affinity ligands.…”
Section: Discussionsupporting
confidence: 55%
“…[12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus). This is clearly superior to previous results by Stokes et al 11 and comparable to test-retest parameters obtained with high-affinity ligands.…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, this divergence also suggests that even though the results of our cluster analysis were highly robust, different striatal zones may have emerged had we performed it on a measure other than coactivation. Interestingly (59), found that patterns of striatal dopamine release did not converge with structural subdivisions, but with corticostriatal activation patterns, which were also the basis of our parcellation (SI Appendix, Fig. S12 shows results based on the NeuroSynth database).…”
Section: Discussionmentioning
confidence: 81%
“…These ROIs are based on the topography of functionally distinct cortico-striatal-thalamo-cortical circuits in non-human primates (Haber, 2010). According to a recent delineation of striatal subregions based on corticostriatal connectivity in humans (Tziortzi et al, 2013), our peak voxels of DA release in the AST map onto loci connected with prefrontal executive cortical areas; peak voxels in SMST map onto loci connected with executive and premoter regions. Thus, it is plausible that the group differences in DA release in these striatal regions are linked with executive and motor control, but not with motivation and reward.…”
Section: Discussionmentioning
confidence: 99%